Temperature rise after peginterferon alfa-2a injection in patients with chronic hepatitis C is associated with virological response and is modulated by IL28B genotype - Han, Hwalih (2013)
BACKGROUND & AIMS: Interferon treatment for chronic hepatitis C is associated with non-specific symptoms including fever. We aimed to determine the association of temperature changes with interferon antiviral activity. METHODS: 60 treatment-naïve patients with chronic hepatitis C (67% genotype 1/4/6, 33% genotype 2/3) were admitted to start peginterferon alfa-2a and ribavirin in a clinical trial. Temperature was measured at baseline and 3 times daily for the first 24 h and the maximal increase from baseline during that time (Δ T(max)) was determined. Serum HCV-RNA, interferon-gamma-inducible protein-10 (IP-10) and expression of interferon-stimulated genes (ISGs – CD274, ISG15, RSAD2, IRF7, CXCL10) in peripheral blood mononuclear cells (PBMCs) were measured at very early time points, and response kinetics calculated. The IL28B single nucleotide polymorphism, rs12979860, was genotyped. RESULTS: Temperatures rose by 1.2 ± 0.8 °C, peaking after 12.5 h. ΔT(max) was strongly associated with 1st phase virological decline (r = 0.59, p <0.0001) and was independent of gender, cirrhosis, viral genotype or baseline HCV-RNA. The association with 1st phase decline was seen in patients with rs12989760CC genotype (r = 0.65, p <0.0001) but not in CC/CT (r = 0.13, p = 0.53) and patients with CC genotype had a higher ΔT(max) (1.4 ± 0.8 °C vs. 0.8 ± 0.6 °C, p = 0.001). ΔT(max) was associated with 6- and 24-h induction of serum IP-10 and of PBMC ISG expression, but only in patients with rs12989760CC. ΔT(max) weakly predicted early virological response (AUC = 0.68, CI 0.49–0.88). CONCLUSIONS: Temperature rise following peginterferon injection is closely associated with virological response and is modulated by IL28B polymorphism, reflecting host interferon-responsiveness. Published by Elsevier B.V. on behalf of the European Association for the Study of the Liver.